Genome sequencing of two iBell pepper endornavirus/i (BPEV) variants infecting iCapsicum annuum/i in Colombia (2017)
Transcriptome analysis of chili and bell pepper samples from commercial plots in the municipalities of Santa Fe de Antioquia and El Penol in the province of Antioquia revealed the presence of viral sequences with significant similarity to genomes of members of the genus Endornavirus. Assembly of the chili and bell pepper transcriptomes resulted in consensus sequences of 14,727 nt and 14,714 nt that were identified as Bell pepper endornavirus (BPEV). Both sequences were nearly identical by 99.9 % at both nucleotide and amino acid levels. The presence of BPEV was confirmed by RT-qPCR, RT-PCR and Sanger sequencing using RdRp-specific primers designed from the assembled sequences in ten independent random samples taken from the investigated bell pepper stands. The phylogenetic analysis of both BPEV variants and their affiliation within the genus Endornavirus is discussed. For our knowledge, this is the first study on this group of viruses in Colombia.